Impact of COVID-19 pandemic on consumer buying behaviour - Nurin Aina Akmal, Abd Malik (2022)
The purpose of this study is to provide a conceptual framework for examining the factors that lead impacts university students to engage in panic buying. The findings reveal 2 different panic buying behaviors among students which is stockpiling and impulsive buying. This is quantitative study whereby convenience sampling was conducted to a total of 380 respondents from Universiti Utara Malaysia (UUM). The research provides a deeper understanding of panic buying behavior The most significant limitation is that this research is conceptual in nature and was unable to experimentally validate the association between variables. These findings contribute to an expanding knowledge base on panic buying behavior and assist other researchers in designing their own studies on panic buying. Future research should investigate if the study should be extended to a larger population in order to get data from all Malaysian consumers. The importance and originality of this research is that it examines the impact of COVID-19 towards panic buying behavior among impacts university students.